Strategi Kepala Sekolah Dasar Negeri dalam Meningkatkan Kompetensi Pedagogik Guru Pendidikan Agama Islam: Public Elementary School Principals’ Strategy for Improving the Pedagogic Competence of Islamic Education Teachers - Sulhikma Jaya; Abdul Halik (Al-Musannif, 2023)
This study examines the pedagogic competence of Islamic education teachers, the principal’s strategy, constraints and solutions. The aim is to find problems, solutions, and strategies implemented by principals of public elementary schools to improve teachers’ pedagogic competence. This research method is qualitative with a phenomenological approach. This research's informants are school principals and Islamic education teachers. The results of the study are: first, the teacher masters the curriculum, learning theory and principles, is able to organize learning, is communicative, empathetic, polite, evaluates, and follows up; second, increasing teacher competence through workshops, supervision, mentoring, further study, and participating in training; third, the obstacle is the lack of teacher training, facilities and infrastructure, and teacher commitment. The solutions are to activate MGMP meetings, continue studies, workshops, monitoring, and school meetings. The research implication is that school principals must carry out their main duties properly, and teachers, as partners, carry out educational tasks in schools.